Pengendalian Salinitas Pada Air Menggunakan Metode Fuzzy Logic - Mubarok, Fahmi; Harianto, Harianto; Wibowo, Madha Christian (JAVA Journal of Electrical and Electronics Engineering, 2015)
some fish farmers has been doing some way of controlling salinity in the water for marine fish farming, the farmers will turn on the water pump when they found the taste of the water used to grow fish is not salty, this indicates that the levels of salinity in the water too low. With this method will certainly lead to the growth of fish disturbed. So monitoring and adjusting the condition of pond water is continuously required to maintain water salinity. In this research we analyze one of the supporting factors for the cultivation of marine fish by adjusting the amount of salinity in the water and maintain it in accordance with the needs of tiger grouper. Using Arduino Uno R3 as a data processor, water level or salinity sensor as measuring salinity and input system, while for the actuator system using DC water pump. Salinity measurements using the water level or salinity sensor has an accuracy rate of 98.99%. Calculation of salinity by using fuzzy method goes well with a 100% success rate in accordance with the fuzzy analysis manually. By using salt water pump system can work well in controlling salinity and maintain between 30-33 ppt salinity.